Intractable diarrhoea of infancy and latent otomastoiditis. Issue 12 (December 1980) - Salazar de Sousa, J; da Silva, A; da Costa Ribeiro, V
Abstract : In 16 infants with intractable diarrhoea, latent otomastoiditis was found in 9 (3 at necropsy and 6 at myringotomy-antrotomy). In 5 of the 6 operated group, surgery was followed by a striking cessation of the diarrhoea and with weight gain. It is concluded that (1) latent otomastoiditis may be a perpetuating factor in intractable diarrhoea; (2) myringotomy-antrotomy should be considered if other forms of treatment have failed, and especially if there is leucocytosis; (3) mastoiditis with diffuse osteitis seems to be associated with a poor prognosis.